A Revisit to the Research Updates of Drugs, Vaccines, and Bioinformatics Approaches in Combating COVID-19 Pandemic - Sumon, Tofael Ahmed; Hussain, Md. Ashraf; Hasan, Md. Tawheed; Hasan, Mahmudul; Jang, Won Je; Bhuiya, Eleus Hussain; Chowdhury, Abdullah Al Mamun; Sharifuzzaman, S. M.; Brown, Christopher Lyon; Kwon, Hyun-Ju; Lee, Eun-Woo (Frontiers in Molecular Biosciences, 2021)
A new strain of coronavirus SARS-CoV-2 responsible for COVID-19 pandemic was first detected in the city of Wuhan in Hubei province, China in late December 2019. To date, more than one million deaths and nearly 57 million confirmed cases have been recorded across 220 countries due to COVID-19, which is the greatest threat to global public health in our time. Although SARS-CoV-2 is genetically similar to other coronaviruses, i.e. SARS and MERS-CoVs, no confirmed therapeutics are yet available against COVID-19, and governments, scientists and pharmaceutical companies worldwide are working together in search for effective drugs and vaccines. Repurposing of relevant therapies, development of vaccines and using bioinformatics to identify potential drug targets are strongly in focus to combat COVID-19. This review deals with the pathogenesis of COVID-19 and its clinical symptoms in humans including the most recent updates on candidate drugs and vaccines. Potential drugs (remdesivir, hydroxychloroquine, azithromycin, dexamethasone) and vaccines (mRNA-1273, MMR, BCG) in human clinical trials are discussed with their composition, dosage, mode of action and possible release dates according to the trial register of US National Library of Medicines (clinicaltrials.gov), European Union (clinicaltrialsregister.eu) and Chinese Clinical Trial Registry (chictr.org.cn) website. Moreover, recent reports on in silico approaches like molecular docking, molecular dynamics simulations, network-based identification and homology modelling are included, toward repurposing strategies for the use of already approved drugs against newly emerged pathogens. Limitations of effectiveness, side effects and safety issues of each approach are also highlighted. This review should be useful for the researchers working to find out an effective strategy for defeating SARS-CoV-2.